Help From a Friend: Helicopter Parenting Predicts Empathy and Bystander Intervention. Issue 19 (October 2022) - Hayes, Katey; Turner, Lisa A.
Harassment toward others happens in many contexts with a myriad of negative impacts on victims, witnesses, and society. Although preventing harassment of others is ideal, it is also important to consider how bystanders may react in ways to defend the victim and reduce the harassment. Bystanders differ in their reactions to these events and the goal of this investigation is to better understand individual differences in college students' reported tendency to defend victims of harassment. We proposed a mediation model where higher rates of helicopter parenting would predict lower empathic concern and greater personal distress. In turn, lower empathic concern and greater personal distress would predict lower likelihood of defending the victim. College students ( n = 305) completed self-report measures of helicopter parenting, empathic concern, personal distress, and bystander intervention to general harassment. Using the Hayes PROCESS program, we found the relation of helicopter parenting to bystander intervention was mediated by empathic concern, such that helicopter parenting predicted lower empathic concern, which predicted lower likelihood of intervening. Helicopter parenting predicted greater personal distress, but personal distress did not predict bystander intervention. In an exploratory analysis, we tested a moderated mediation model in which personal distress moderated the relation of empathic concern to bystander intervention. The moderated mediation model was statistically significant; for students with low to moderate personal distress, empathic concern predicted self-reported intervention. However, for students high in personal distress, empathic concern was not related to self-reported intervention. The current study explained a small amount of the variance in bystander intervention. These findings demonstrate the complex family and personal factors that may explain, to a small degree, individual differences in bystander intervention. Further studies should consider the complex contextual variables that may influence this relationship.